PARADIGMA DAN LANDASAN BIMBINGAN KONSELING DALAM PENGEMBANGAN KECERDASAN DI SMA PARIWISATA BANDUNG - Ayi Najmul Hidayat; Agus Hermawan; Tati Ratna Wulan; Aceng Nurul Huda (Tadbir: Jurnal Manajemen Pendidikan Islam, 2026)
This research was conducted to find out how counseling guidance services can develop the intelligence of Bandung Tourism High School students. The object of the research is grade XI students of Bandung Tourism High School. The type of research used in this study is field research or field research which is qualitative descriptive research. Data collection techniques with interviews, observations and documentation. The data collection technique consists of data reduction, data presentation and conclusion drawn. The results of the study show that the paradigm of BK services at Tourism High School has shifted towards development and prevention, no longer just curative. BK teachers position themselves as facilitators of students' personal growth, who accompanies not only when students have problems, but from the beginning of the educational process, The implementation of BK services in the school is based on philosophical, psychological, pedagogical and sociological aspects. The development of student intelligence through BK services is carried out in the field of developing intellectual intelligence, fostered through tutoring and achievement monitoring. Emotional and social intelligence is developed through counseling and group activities such as mentoring. Spiritual intelligence is strengthened through moral development programs and Islamic guidance that synergize with PAI teachers. This approach supports Gardner's idea of a compound intelligence, and also affirms the role of Islamic education in shaping human beings. Although it has been running quite effectively, there are still challenges such as limited counseling room facilities and the need to increase the professional capacity of BK teachers, especially in the use of technology and strengthening Islamic values-based approaches.